Benzedeiras : entre o ofício do cuidar, patrimônio e hibridismo cultural - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This technical report addresses the spectrum of the history of healers as intangible cultural heritage, covering their work in popular culture and folk medicine and in the rescue of memory and identity. The central objective of this research is to draw a timeline that runs through the development of this practice over time until the present day. For centuries, knowledge related to blessings was transmitted from generation to generation, rooting itself in orally practices and rituals. This transmission established a fundamental link between people and their cultural heritage, reflecting the deep connections between tradition and community. However, as modern society progressed, new forms of communication and education entered the scene, playing a transforming role in this context. The research explores how healers, over time, have adapted their practices to social and technological changes. The research will verify how contemporary healers found ways to incorporate new tools, such as digital media and cultural events, to preserve and share their traditional knowledge. In this sense, the research highlights not only the evolution of the craft of healers, but also the resilience and adaptability of these emblematic figures as they continue the ancestral tradition in a world in constant transformation.
Benzedeiras : between the work of care, heritage and cultural hybridity
Keywords: Benzedeiras; Patrimônio cultural; Hibridismo cultural; Atualidade; Cultural heritage; Cultural hybridity; Current affairs; CIENCIAS HUMANAS::HISTORIA